Dielectric supported bimetal layer configuration for long-range surface plasmon polariton interference–based subwavelength lithography - Prabhathan, Patinharekandy (2015)
Long-range surface plasmon polariton (LRSPP) interference in a dielectric supported bimetal layer configuration is analyzed for nanoscale periodic feature fabrication. The single metal layer in a conventional configuration has been split into a bimetal layer configuration supported by a dielectric layer to enable LRSPP interference in different layers. It is shown that the configuration can be implemented in two different ways to record the interference pattern with high exposure depth and high contrast. Subwavelength periodic pattern having a half-pitch resolution of 65 nm at 446-nm wavelength is illustrated with the proposed two-beam and four-beam LRSPP interference configurations.